PERAN MAJELIS PERMUSYAWARATAN ULAMA (MPU) DALAM MEMBANGUN MODERASI BERAGAMA DI PROVINSI ACEH - Lismijar, Lismijar (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2026)
The Aceh MPU is an important element in realizing religious moderation in Aceh, because the Aceh MPU has significant authority and function in overcoming religious problems in society. Therefore, this research aims to determine the role of the MPU in building religious moderation in Aceh. This research uses a qualitative approach with a descriptive method, where the researcher goes directly to the research location, then the data from the analysis is presented and discussed using data collection techniques through observation, interviews and documentation. The research results show that the MPU's role in building religious moderation in Aceh is (1) in accordance with its duties and authority, the Aceh MPU participates in building religious moderation in Aceh, one of which is through the issuance of Aceh MPU Fatwa No. 5 of 2019 which regulates intolerance and radicalism according to Islamic Sharia and local wisdom, in this case the Aceh MPU issues a fatwa haram against radicalism, (2) provides guidance and advice to the community, (3) carries out cadre education and becomes a resource person in every educational implementation Ulama cadres implemented by the City Regency MPU, (2) provide enlightenment on the importance of tolerance in maintaining harmony and peace among the people through various discussion forums and religious dialogue. The obstacles faced by the Aceh MPU in developing religious moderation in Aceh are (1) lack of public understanding of the importance of religious moderation, (2) excessive development of religious understanding and practice in society.